BIM for FM: Developing information requirements to support facilities management systems. Issue 5 (21st November 2019) - Matarneh, Sandra T.; Danso-Amoako, Mark; Al-Bizri, Salam; Gaterell, Mark; Matarneh, Rana T.
Abstract : Purpose: This paper aims to identify a generic set of information requirements for facilities management (FM) systems, which should be included in BIM as-built models for efficient information exchange between BIM and FM systems, and to propose a process to identify, verify and collect the required information for use in FM systems during the project's lifecycle. Design/methodology/approach: Both qualitative and quantitative approaches were applied at different stages of the study's sequential design. The collection and analysis of qualitative data was based on an extensive literature review of similar studies, standards, best practices and case study documentation. This was followed by a questionnaire survey of 191 FM practitioners in the UK. This formed the background of the third stage, which was the development of the information management process to streamline information exchange between building information models and FM systems. Findings: The study identifies a generic list of information requirements of building information models to support FM systems. In addition, the study presents an information management process that generates a specific database for FM systems using an open data format. Originality/value: The existing literature focuses on specific building types (educational buildings) or specific information requirements related to particular systems (mechanical systems). The existing standards, guidelines and best practices focus on the information requirements to support the operations and maintenance (O&M) phase in general. This study is different from previous studies because it develops a set of specific information requirements for building information models to support FM systems. FM organisations and owners can use the proposed list of information requirements as a base to generate specific data output for their FM systems' input, to decrease the redundant activity of manual data entry and focus their efforts on key activities.